Quantitative evaluation of malignant gliomas damage induced by photoactivation of IR700 dye. Issue 1 (1st January 2016) - Sakuma, Morito; Kita, Sayaka; Higuchi, Hideo
Abstract: The processes involved in malignant gliomas damage were quantitatively evaluated by microscopy. The near-infrared fluorescent dye IR700 that is conjugated to an anti-CD133 antibody (IR700-CD133) specifically targets malignant gliomas (U87MG) and stem cells (BT142) and is endocytosed into the cells. The gliomas are then photodamaged by the release of reactive oxygen species (ROS) and the heat induced by illumination of IR700 by a red laser, and the motility of the vesicles within these cells is altered as a result of cellular damage. To investigate these changes in motility, we developed a new method that measures fluctuations in the intensity of phase-contrast images obtained from small areas within cells. The intensity fluctuation in U87MG cells gradually decreased as cell damage progressed, whereas the fluctuation in BT142 cells increased. The endocytosed IR700 dye was co-localized in acidic organelles such as endosomes and lysosomes. The pH in U87MG cells, as monitored by a pH indicator, was decreased and then gradually increased by the illumination of IR700, while the pH in BT142 cells increased monotonically. In these experiments, the processes of cell damage were quantitatively evaluated according to the motility of vesicles and changes in pH. Abstract : UF0001 Phototoxicity of IR700 dye conjugated with anti-CD133 antibody to gliomas was evaluated quantitatively by the measurement of vesicle fluctuation and pH indicator.